Comparative evaluation of pre-infusion at caesar section performed under spinal anesthesia. Results of multicenter trial (Pain medicine, 2020)
Abstact. Study of the effect of preinfusion, various infusion solutions on the state of hemodynamics, in patients undergoing a cesarean section performed under spinal anesthesia with 0.5 % solution of Longocain Heavy (0.5 % hyperbaric bupivacaine).Materials and methods. Spinal anesthesia (SAN) was performed in 2 190 women, aged 21 to 39 years, with a gestational age of 39 to 40 weeks. The structure of extragenital pathology was dominated by chronic anemia of varying severity – 1 650 (75.3 %), urinary tract infections – 756 (34.5 %), mild preeclampsia – 245 (11.2 %), chronic nonspecific lung diseases – 125 (5.7 %). 1 786 (81.5 %) patients underwent surgery in a planned manner, according to emergency indications – 404 (18.4 %). A combination of the two pathologies was observed in 852 (38.9 %) women. Indications for surgery were: disease of the operated uterus, insolvency of the scar on the uterus, clinically narrow pelvis, high-grade myopia, secondary labor weakness. The duration of surgery is ranged from 40 to 52 minutes.Results. In group I, the expressed hypotension, requiring sympathomimetic support with mezaton was observed in 192 (34.8 %) patients. In group II, severe hypotension requiring sympathomimetic support with mezaton was observed in 114 (20.8 %) patients. And in group III, hypotension requiring sympathomimetic support with mezaton was observed in 127 (23.2 %) patients. At that time, in patients of group IV severe hypotension, requiring sympathomimetic support with mezaton was observed in only 91 (18 %) cases.Conclusions. Neuraxial anesthesia is accompanied by the development of hypotension, which can be prevented by preinfusion with crystalloid solutions. Aggressive preinfusion of large volumes of isoosmolar crystalloids at a dose of 10–14 ml/kg was associated with an increase in the frequency of hemodynamic instability requiring sympathomimetic support.
Keywords: spinal analgesia; bupivacaine; rheosorbilact; cesarean section